The "value added" of neurocognitive testing after sports-related concussion - Van Kampen, D. A.; Lovell, M. R.; Pardini, J. E.; Collins, M. W.; Fu, F. H. (The American Journal of Sports Medicine, 2006)
Background: Neurocognitive testing has been endorsed as a "cornerstone" of concussion management by recent Vienna and Prague meetings of the Concussion in Sport Group. Neurocognitive testing is important given the potential unreliability of athlete self-report after injury. Relying only on athletes` reports of symptoms may result in premature return of athletes to contact sport, potentially exposing them to additional injury.